تدبير اندحاق جدار البطن الأمامي باستخدام رقعة البرولين - علي, ماجد; مسعود, سجيع; أحمد, باسل (Latakia University Journal -Medical Sciences Series, 2019)
· شملت هذه الدراسة 51 مريضاً تمّ قبولهم وعلاجهم في مشفى الأسد الجامعي في اللاذقية قسم الجراحة. 37 أنثى (72.54℅) و14 ذكراً (27.46℅). تراوحت أعمار المرضى بين سنة و 90 سنة بعمر وسطي 47.34. · لاحظنا في دراستنا زيادة نسبة الاندحاق مع التقدّم بالعمر, كما أنّ الإناث كنّ أكثر تأهّباً للاندحاق من الذكور بنسبة 2.6-1. · أظهرت الدراسة أنّ الشقّ الناصف هو أكثر الشقوق تأهّباً للاندحاق 32 مريضاً بنسبة 62.75℅، وأنّ شقوق الخطّ الناصف أسفل السرّة أكثر تأهّباً للاندحاق من أعلى السرّة بنسبة 73.33%. · إنّ أكثر الأمراض المرافقة للاندحاق هي الأمراض القلبية وارتفاع التوتر الشرياني بنسبة 27.45℅ والداء السكري بنسبة 13.73℅ والأمراض الرئوية بنسبة 13.73℅. · إنّ للبدانة دوراً مهماً في التأهّب للاندحاق بنسبة 66.67 ℅. · تمّ تقسيم المرضى حسب مكان وضع الرقعة إلى مجموعتين: الأولى: تمّ وضع رقعة البرولين خلف السفاق وضمّت 22 مريضاً, والثانية: تمّ وضع رقعة البرولين أمام السفاق وشملت 28 مريضاً، إضافةً لحالة وحيدة تمّ وضع الرقعة فيها أمام وخلف السفاق. · This study included 51 patients (37 females (72.54%) and 14 males (27.46%)) admitted and treated in the Department of Surgery at Al-Assad University Hospital in Lattakia. Patients were between 1 and 90 years old (the average was 47.34 years). · We noted in our study that incisional hernia ratio increased with age. Females were more affected than males in a proportion of 2.6 – 1. · It was clear that midline incision hernias were much more than hernias of other incisions (32 patients (62.75%) especially under umbilicus, (73.33% of midline incision hernias). · The most predisposing diseases were cardiac diseases and HBP (27.45%), and to a lesser extent DM and pulmonary diseases (13.73% each). · Obesity played a great role in incisional hernias (66.67%). · Patients were divided into two groups according to the patch site; in the first group (including 22 patients), the prolene patch was placed posterior to aponeurosis. In the second one (comprising 28 patients), the patch was placed anterior to aponeurosis. And in a single case, the patch was put posterior and anterior to aponeurosis.